Pests infesting ornamental plants in hilly region of West Bengal (The Journal of Plant Protection Sciences, 2020)
The survey was conducted during 2005-07 at the farms of R.R.S., UBKV, Kalimpong; R.R.S.S.,  UBKV, Pedong and other adjoining areas. The Crops surveyed included gladiolus, carnation, anthurium  gerbera, china rose, chrysanthemum, Bird of Paradise, Straw flower. A number of aphid species were  found infesting different ornamental plants viz. Myzus persicae on Carnation, gerbera and Anthurium; Macrosiphoniella sanborni on Chrysanthemum; Aphis gossypii on China rose. Other sucking pests  infesting ornamentals included Bemisia tabaci on Gerbera, leafhopper on Gladiolus and scale insect  (unspecified) on Anthurium. Amongst the thysanopteran pests Taeniothrips simplex was very much  serious on Gladiolus and another species of thrips (unspecified) was found infesting Carnation.
Keywords: Ornamental; UBKV; Chrysanthemum